A morphology controlled surface sulfurized CoMn2O4 microspike electrocatalyst for water splitting with excellent OER rate for binder-free electrocatalytic oxygen evolution. Issue 20 (14th May 2021) - Bahadur, Ali; Hussain, Waseem; Iqbal, Shahid; Ullah, Farman; Shoaib, Muhammad; Liu, Guocong; Feng, Kejun
Abstract : Facile synthesis of sulfurized CoMn2 O4 microspikes, showing good stability and excellent OER activity for water splitting. Abstract : Transition metal mixed oxides have drawn extensive interest as oxygen evolution electrocatalyst alternatives to noble metal-based materials but generally involve prolonged synthesis routes and limited electrocatalytic activity and stability. Herein we report surface sulfurized CoMn2 O4 microspikes (S–CoMn2 O4 -MSs) grown directly at low temperature and ambient atmosphere using a two-step facile synthesis protocol, requiring only 310 s. S–CoMn2 O4 -MSs showed excellent OER activity with an overpotential of 300 mV at 10 mA cm −2 while pristine Mn3 O4 and Co3 O4 required 580 and 410 mV to deliver the same current density value. Moreover, we rationally designed the study to gradually decrease the Tafel slope value from 307.5 to 26.2 mV dec −1 for the best electrocatalyst, with excellent stability at 20 mA cm −2 for 24 h without any binder. This overall performance compares well with very recently reported oxides and CoMn2 O4 based systems and the as-synthesized material showed highly competitive overall performance. During this work, the stability of the S 2− layer remained the main concern and was confirmed by several characterization techniques. We investigated the surface blockage role of the surface S 2− layer and, therefore, optimized the degree of sulfurization for best performance. In the end, we attributed and supported the exciting performance of S–CoMn2 O4 MSs to the synergistic effect of Co and Mn, their unique morphology, the easily oxidizable lower oxidation states of cobalt (due to surface sulfurization treatment), and the large interior structure for increased contact with the electrolyte.